PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) TERHADAP KEMAMPUAN MENULIS TEKS NARATIF (CERITA RAKYAT) BERBASIS KEARIFAN LOKAL PADA MAHASISWA SEMESTER II PENDIDIKAN BAHASA INGGRIS UNIVERSITAS CITRA BANGSA - Selfiana Triyanty M. Ndapa Lawa; Roswita Lioba Nahak; Viktorius Paskalis Feka (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2023)
This study aims to determine the influence of problem-based learning model/PBL towards narrative text (folklore) writing ability based on local wisdom in second semester students of English Education Study Program in Citra Bangsa University (UCB). This study applies a quantitative approach with a quasi-experimental design. The sampling technique uses saturation sampling (census) where the total population is less than 30 therefore the total sample in this study is the same as the total population, 20 students. Data collection technique uses an essay test. Before the instrument is distributed, there are validity and reliability tests to obtain the validity of the instrument. The results of the validity test shows that 20 items are valid and reliable/consistent. The hypothesis analysis requirements test consists of normality test, data homogeneity and data analysis techniques using the t-test. The results of the data normality test show that the sig. in the control class 0.333> 0.05 and the experimental class 0.366> 0.05 so that both are normally distributed. While the results of the homogeneity test show that the probability value is 0.449> 0.05, then the two classes can be said to be homogeneous. The results of the difference test on the average of writing ability of narrative text (folklore) based on local wisdom for the control class and the experimental class show that the average of writing ability of narrative text (folklore) based on local wisdom for the experimental class is higher than the average of writing ability of narrative text (folklore) based on local wisdom of the control class, which is 85.35> 77.15 and the score of sig. on the independent t-test shows a result of 0.000 <0.005. In conclusion, Problem-Based Learning model influences narrative text (folklore) writing ability based on local wisdom in second semester students of English Education Study Program in Citra Bangsa University (UCB).